2009
DOI: 10.1016/j.fertnstert.2008.02.121
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of biomarkers associated with the implantation window in women with endometriosis

Abstract: Objective-To evaluate the expression of biomarkers of implantation, Glycodelin A (GdA), Osteopontin (OPN), Lysophosphatidic acid receptor 3 (LPA3), and HOXA10, in eutopic endometrium of women with and without endometriosis.Design-Prospective observational study. Setting-Clinical Research Center.Patient(s)-Twenty-four women with endometriosis and 23 healthy volunteers of similar age. Intervention(s)-Secretory phase endometrial biopsy.Main Outcome Measure(s)-Expression of immunohistochemical staining intensity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
3
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 30 publications
4
93
3
9
Order By: Relevance
“…Impairment in the receptive status of the endometrium in women with endometriosis is well evidenced [45,46]. It appears that both the endometrium and the oocyte/embryo are affected in endometriosis, and it remains to be unraveled as to which factor is more important in adversely affecting the pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in the receptive status of the endometrium in women with endometriosis is well evidenced [45,46]. It appears that both the endometrium and the oocyte/embryo are affected in endometriosis, and it remains to be unraveled as to which factor is more important in adversely affecting the pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that the expression of epithelial avb3 is associated with the window of implantation and that the endometrium is devoid of this particular integrin in certain cases of infertility (Lessey et al, 1992;Castelbaum et al, 1994), endometriosis (Lessey et al, 1994;Lessey, 2002;Wei et al, 2009;Casals et al, 2012), and idiopathic infertility (Lessey et al, 1995). The level of integrin b3 mRNA on day 21 has been suggested as a possible indicator with which to predict success rates following ART, while avb3 has been considered as a clinical biomarker for human implantation (Elnashar and Aboul-Enein, 2004).…”
Section: Endometrial Integrinsmentioning
confidence: 99%
“…-интерлейкина-1, -6, -11 (IL-I, -6, -11) [45,46]; -лейкемияингибирующего фактора (LIF) [47]; -сосудисто-эндотелиального фактора роста (VEGF) [48]; -гепаринсвязывающего эпидермального фак-тора роста (ГС-ЭФР) [49]; -матриксных металлопротеиназ (ММР) и их тканевых ингибиторов (ТIMP) [50]; -интегринов [46,47]; -селектинов [51,52]; -гликоделина A [53]; -кадгеринов [45]; -муцинов [45]; -простагландинов [54]; -белка Ki-67 [55,56]. Перечисленные молекулярные маркеры могут определяться в крови, секрете эндометрия или в са-мой ткани эндометрия, полученной при его биопсии.…”
Section: проблемы репродукции 5 2016unclassified